ISLAMIC POLITICAL ECONOMY IN FOREST RESOURCE MANAGEMENT: AN ANALYSIS OF DEFORESTATION AND ILLEGAL LOGGING IN INDONESIA - Sugeng Riyadi (International Journal of Multidisciplinary Reseach, 2026)
Indonesia, with its rich tropical forests, faces serious threats from deforestation and illegal logging, impacting both the environment and society. This article analyzes the problems of deforestation and illegal logging in Indonesia through the lens of Islamic political economy. By examining the ecological and socio-economic impacts, as well as weaknesses in forest governance, this research offers solutions based on Islamic values. The concepts of ownership (milkiyyah) as a trust (amanah), the principle of public interest (maslaha), and the role of humans as vicegerents (khalifah) on earth serve as the ethical foundation. Empirical data reveal an alarming rate of deforestation, even within legal concession areas. Proposed solutions include fair law enforcement, community-based oversight (hisbah), Islamic environmental education, local economic empowerment, public policies based on maslaha, and the utilization of Islamic financial instruments such as green sukuk. This article concludes that the deforestation crisis is not merely a technical issue, but also an ethical and spiritual crisis demanding comprehensive transformation based on Islamic teachings to achieve sustainable forest management.